Структура системы поддержки дистанционного обучения в заведениях профтехобразования - Бондаренко, Т. С.; Кожевников, Г. К. (Видавництво НГУ, 2016)
В работе описывается структура система поддержки дистанционного обучения в заведениях профтехобразования и особенности ее построения на базе облачных сервисов. Рассматриваются преимущества и недостатки предложенного под‐хода к построению системы дистанционного обучения.

The paper describes the structure of system of support distance learning in vocational training institutions and features of its construction based on cloud services. The advantages and disadvantages of the proposed approach to the construction of a distance learning system are listed.
The structure of remote sestem of distance education in institutions of vocational training
Keywords: дистанционное обучение; профтехобразование; облачные сервисы; система дистанционного образования; distance learning; vocational education; cloud services; system of distance learning